Editorial Hope for Type 1 Diabetic Patients - Shams uddin Shaikh, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2011)
Diabetes mellitus, a common metabolic disorder. It's number is increasing day by day, the reasons may be many, increasing overall population. increased life expectancy of a diabetic patient due to number of options in the management and cure, above all is the awareness and so the early detection of the disease.